Antihypertensive Drug Utilization in Two Districts of Northern Cyprus - M. Tamirci; R. Demirdamar (Рациональная фармакотерапия в кардиологии)
Aim. Since the irrational use of medicine increases the risk of morbidity and mortality in hypertension, this study was aimed to evaluate antihypertensive pharmacotherapy at two districts of Northern Cyprus (NC).Material and methods. A total of 148 prescriptions including antihypertensive drugs (n=181) were obtained by the aid of five pharmacists between November 2017 August 2018 and evaluated regarding the antihypertensive drug choices and good prescribing principles. The prescribed antihypertensive agents were classified according to the Anatomical Therapeutic Chemical Classification System (ATC) 2, 3 and 5 and the prescriptions were evaluated regarding the availability of format information.Results. The mean of antihypertensive agents per prescription was 1.2±0.6. According to the ATC-3 subclassification, beta-blockers (22.1%), angiotensin receptor blockers (ARBs) (22.1%), calcium channel blockers (20.4%), angiotensin converting enzyme inhibitor (ACE) inhibitors (17.7%), diuretics (13.8%) and anti-adrenergic drugs (3.9%) were prescribed. According to the ATC-5 subclassification, the most common prescribed antihypertensives were metoprolol (16.6%), amlodipine (16.0%), furosemide (8.8%), captopril (7.7%) and losartan (6.6%). There were no significant relation between the prescribed antihypertensive agents and gender and the physicians serving either in governmental or private hospitals. There were shortcomings in the prescriptions such as age, diagnosis and drug information which were crucial for the chosen of an appropriate antihypertensive agent.Conclusion. This first pharmacoepidemiological study about antihypertensive drug utilization in NC indicates the imperfections of physicians in terms of prescribing antihypertensive agents according to the guidelines and writing a “legible and good” prescription that contains full information. These findings underline necessity of educational interventions for physicians to disseminate rational use of medicine (RUM) in the NC.